2010
DOI: 10.1155/2010/364508
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Y-Chromosomal Complement in the Majority of Gestational Trophoblastic Neoplasms

Abstract: Gestational trophoblastic neoplasms (GTNs) are a rare group of neoplastic diseases composed of choriocarcinomas, placental site trophoblastic tumors (PSTTs) and epithelioid trophoblastic tumors (ETTs). Since these tumors are derivatives of fetal trophoblastic tissue, approximately 50% of GTN cases are expected to originate from a male conceptus and carry a Y-chromosomal complement according to a balanced sex ratio. To investigate this hypothesis, we carried out a comprehensive analysis by genotyping a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Interestingly, more than 85% of patients with PSTT have had a female antecedent gestation either by history or genetic analysis. Furthermore, PSTTs lack Y chromosomes based on a molecular genetic analysis, suggesting a role of the paternally derived X chromosome in the pathogenesis of PSTT [36,61,77,83,178]. Alternatively, this shortfall of Y-chromosomal complements in PSTTs may reinforce the notion that the majority of PSTTs are derived from previous molar gestations.…”
Section: Placental Site Trophoblastic Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, more than 85% of patients with PSTT have had a female antecedent gestation either by history or genetic analysis. Furthermore, PSTTs lack Y chromosomes based on a molecular genetic analysis, suggesting a role of the paternally derived X chromosome in the pathogenesis of PSTT [36,61,77,83,178]. Alternatively, this shortfall of Y-chromosomal complements in PSTTs may reinforce the notion that the majority of PSTTs are derived from previous molar gestations.…”
Section: Placental Site Trophoblastic Tumormentioning
confidence: 99%
“…However, the case number in that study is limited to permit from conclusions. The absence of Y chromosome has been demonstrated in the vast majority of choriocarcinomas, indicating that the shortfall of Y chromosomal complements in choriocarcinomas may simply be due to the genetic basis of their precursor lesions, complete hydatidiform moles in which most of cases had the genotype of XX [178].…”
Section: Clinicopathological Features Behavior and Treatment Of Trophoblastic Tumors And Tumor-like Lesions Choriocarcinomamentioning
confidence: 99%
“…Approximately half of ETT cases and 40% of PSN cases are located in the lower uterine segment and/or upper endocervix [3,4,9,11,12]. A recent study showed a lack of a Y-chromosome complement in >80% of cases of ETTs [13]. Analysis of the Y allele in PSNs may be helpful to further clarify the relationship between ETTs and PSNs.…”
Section: Discussionmentioning
confidence: 99%
“…11 Absence of Y chromosome complement has been observed in the majority of tumors. 15 However, a comparative genomic hybridizataion study showed an undisturbed genome in three cases. 16 Metastasis occurs in 25% of cases and 10% of patients die of disease.…”
Section: Differentiation Of Ett From Squamous Cell Carcinoma Requiresmentioning
confidence: 96%